Climate Change and Eco-Anxiety in Contemporary Climate Fiction (Cli-Fi) - Nur Affah Al Akromi, Elok; Miakhil, Jan Mohammad (International Journal of Social Research, 2025)
Climate change has precipitated not only an ecological crisis but a profound psychological one, giving rise to eco-anxiety a chronic, multidimensional emotional response to environmental degradation that is increasingly prevalent across global populations. Despite the parallel growth of climate fiction (cli-fi) as a culturally significant literary genre, scholarship has yet to systematically examine how contemporary cli-fi represents eco-anxiety as both thematic content and formal principle. This study addresses that gap through a qualitative ecocritical and affective literary analysis of six internationally significant cli-fi novels: Kingsolver's Flight Behavior (2012), Powers' The Overstory (2018), El Akkad's American War (2017), Jemisin's The Fifth Season (2015), Offill's Weather (2020), and Ghosh's Gun Island (2019). Employing thematic analysis supported by NVivo (Version 14) and guided by an ecocritical coding rubric derived from the eco-anxiety frameworks of Albrecht (2019), Clayton and Karazsia (2020), and Pihkala (2022), the study analyzed 312 coded passages across six eco-anxiety themes. Findings reveal that ecological grief (29.8%) and anticipatory loss (25.6%) constitute the dominant affective registers of the corpus, followed by helplessness and powerlessness (22.1%), solastalgia (21.2%), affective resilience (18.3%), and intergenerational despair (16.7%). The study further demonstrates that eco-anxiety is not merely depicted thematically but formally enacted through narrative fragmentation, temporal disruption, and second-person address. Cross-cultural analysis reveals that postcolonial cli-fi encodes eco-anxiety as inseparable from racial and political dispossession, challenging Western-centric psychological frameworks. The study proposes an original "eco-anxiety poetics" framework with significant implications for ecocritical scholarship, environmental education, climate communication, and therapeutic bibliotherapy practice.